Progress on Optimizing Miscanthus Biomass Production for the European Bioeconomy: Results of the EU FP7 Project OPTIMISC - Lewandowski, Iris; Clifton-Brown, John; Trindade, Luisa M.; van der Linden, Gerard C.; Schwarz, Kai-Uwe; Müller-Sämann, Karl; Anisimov, Alexander; Chen, C.-L.; Dolstra, Oene; Donnison, Iain S.; Farrar, Kerrie; Fonteyne, Simon; et al. (Frontiers in Plant Science, 2016)
This paper describes the complete findings of the EU-funded research project OPTIMISC, which investigated methods to optimize the production and use of miscanthus biomass. Miscanthus bioenergy and bioproduct chains were investigated by trialing fifteen diverse germplasm types in a range of climatic and soil environments across central Europe, Ukraine, Russia and China. The abiotic stress tolerances of a wider panel of 100 germplasm types to drought, salinity and low temperatures were measured in the laboratory and a field trial in Belgium. A small selection of germplasm types was evaluated for performance in grasslands on marginal sites in Germany and the UK. The growth traits underlying biomass yield and quality were measured to improve regional estimates of feedstock availability. Several potential high-value bioproducts were identified. The combined results provide recommendations to policymakers, growers and industry. The major technical advances in miscanthus production achieved by OPTIMISC include: 1) demonstration that novel hybrids can out-yield the standard commercially grown genotype Miscanthus x giganteus; 2) characterisation of the interactions of physiological growth responses with environmental variation within and between sites; 3) quantification of biomass-quality-relevant traits; 4) abiotic stress tolerances of miscanthus genotypes; 5) selections suitable for production on marginal land; 6) field establishment methods for seeds using plugs; 7) evaluation of harvesting methods; and 8) quantification of energy used in densification (pellet) technologies with a range of hybrids with differences in stem wall properties. End-user needs were addressed by demonstrating the potential of optimizing miscanthus biomass composition for the production of ethanol and biogas as well as for combustion. The costs and life-cycle assessment of seven miscanthus-based value chains, including small- and large-scale heat and power, ethanol, biogas and insulation material production, revealed GHG-emission- and fossil-energy-saving potentials of up to 30.6 t CO2eq C ha-1y-1 and 429 GJ ha-1y-1 , respectively. Transport distance was identified as an important cost factor. Negative carbon mitigation costs of -78 € t-1 CO2eq C were recorded for local biomass use. The OPTIMISC results demonstrate the potential of miscanthus as a crop for marginal sites and provide information and technologies for the commercial implementation of miscanthus-based value chains.